COVID-19 Pneumomediastinum: Possible Role of Transesophageal Echo in Bedside Percutaneous Bicaval Double-Lumen ECMO Cannulation in Children. A Case Report - Moscatelli, Andrea; Pezzato, Stefano; Buratti, Silvia; Lampugnani, Elisabetta; Di Mascio, Alberto; Damasio, Maria Beatrice; Caorsi, Roberta; Gattorno, Marco; Castagnola, Elio (Frontiers in Pediatrics, 2021)
COVID-19 is generally uneventful in children. Only 8% of severe acute respiratory distress syndrome corona virus 2 pediatric patients require intensive care, of these 1% may need extracorporeal membrane oxygenation (ECMO). Pre-existing medical conditions are an independent risk factor for pediatric intensive care unit admission. We describe the case of an 11-year-old girl with adenosine deaminase 2 deficiency who presented severe COVID-19 related acute respiratory distress syndrome (ARDS), complicated by a massive air leak syndrome. The ARDS, refractory to conventional respiratory support, required veno-venous ECMO cannulation. To prevent viral diffusion, bicaval double lumen ECMO cannulation was performed percutaneously at the bedside under exclusive echo guidance. Because of the presence of pneumomediastinum, pneumothorax and subcutaneous emphysema, ultrasound visualization of the heart was possible only with trans-esophageal echo. To our knowledge, this is the first description of a trans-esophageal echo guided bedside percutaneous bicaval double lumen ECMO cannulation in a pediatric patient. Pitfalls of the technique are highlighted.